Prevalence of dementia in elderly population in Sarawak using the Early Dementia Questionnaire (EDQ) - Nazeefah, Hamdin; Zurraini, Arabi; Syed Alwi, S.A.R; Helmy, Hazmi (2019)
Introduction: The number of elderlies in Malaysia is increasing similar with the rise in ageing population worldwide. This leads to increase in the prevalence of dementia. This study was done to screen the elderly population in health clinics in Sarawak for dementia using the validated Early Dementia Questionnaire (EDQ). EDQ is a screening tool based on symptoms of dementia. Methods: A cross sectional study was done on the elderly patients aged 60 years and above attending health clinics in Kuching, Sibu and Miri, Sarawak using systematic sampling. Patients with depression were excluded from the study using the Geriatric Depression Scale (GDS). Eligible patients were then assessed for dementia using the validated Early Dementia Questionnaire (EDQ) with the cut-off score of 10. Their informants were also interviewed to complete the questionnaire. Results: The prevalence of dementia among 455 elderly patients was 42.4% (CI 1.180, 2.534). After controlling for confounding factors, dementia was independently associated with advanced age (adjusted OR: 7.3; 95% CI: 1.561, 34.202; P=0.012) and no formal education (adjusted OR: 3.3; 95% CI: 0.198, 0.453; P<0.001). Concentration (75.6%) was the most common symptom presented. Other symptoms were memory symptoms (48.2%), physical and emotional symptoms (57.2%) and symptoms on sleep and environment (50.7%). Conclusion: The prevalence of dementia in Sarawak based on EDQ was 42.2%. Apart from memory problems which are often associated with dementia, patients with concentration problems should also alert the health professionals on the possibility of dementia.